Effect of Music Therapy on Oxygen Saturation Level: A Literature Review - Chakravarty, Ruma; Mehta, Neena; Vir, Dharam (Harmonia: Journal of Arts Research and Education, 2022)
Music therapy as a non-invasive therapeutic modality is gaining prominence worldwide both in hospital settings as an adjunct therapy as well as for community wellbeing. Music therapy offers encouraging evidence-based outcomes for stabilising vital parameters to improve symptoms associated with complex illnesses such as autism spectrum disorder or major depressive disorders. The purpose of this review is to 1) identify scientific literatures that offer insights on the effect of music therapy on oxygen saturation levels of patients undergoing treatments for diverse conditions; 2) compare the effects of music therapy based on identified parameters 3) analyse the critical reviews of the researchers of studies included in this literature scan and 4) synthesise the review findings for the benefit of future scientific researches on the effect of music therapy on oxygen saturation levels. In this review, an analysis of relevant scientific papers published in the last 80 years from 1940 to 2020 (as available) was done by searching databases such as PubMed, Cochrane Library, Wiley Online Library, Gray Literature sources such as Google Scholar, Worldcat; DOAJ, and WHO Global Index Medicus. Eighteen relevant papers describing music therapy’s effect on the patient’s oxygen saturation levels (under different conditions) were included in the review. The results and discussions respectively compare and analyse characteristics of included studies, music therapy administered, measuring device used, the effectiveness of music therapy on oxygen saturation levels, and critical reviews of authors of the scanned literature.